Aplicações e modelagem da resposta ao índice de refração de redes de Bragg em fibras corroídas - Kuhne, Jean Filipe (2022)
This thesis, structured in the format of a collection of scientific articles, addresses the effects of the interaction of the fiber core propagating mode with the external environment in etched Bragg gratings inscribed in optical fibers. Such interaction modulates the fiber Bragg grating (FBG) reflected signal, allowing the perception of the surrounding refractive index. The measurement of this parameter is of great interest because it is associated with the presence, concentration or purity of the substance under investigation. The presented articles address: the modeling and the response of a step index single-mode FBG and of a graded index multi-mode FBG, showing their application to evaluate purity degree of biodiesel samples; models to estimate the response curve of an etched fiber Bragg grating (EFBG); and the birefringence induced over an EFBG coated with an organic film for ammonia detection. The first paper evidences the dependence between the modal field diameter (MFD) of the propagating core mode and the fiber’s sensitivity to the external environment. The greater sensitivity verified in multimode fibers is due to their higher MFD. Higher MFDs imply in smaller fiber reductions over FBG region, implying in an greater mechanical robustness of the sensor when compared to single-mode fiber. It was also verified that the use of multimode fiber allows an increase in the refractive index dynamic range, from 1.456 to 1.476, when compared to single mode fibers. The higher span allows the measurement of substances that have a higher refractive index, typically not detectable by single mode FBG. The biodiesel purity was verified as an application example, allowing to determine its concentration up to the presence of 70% of vegetable oil in the fuel by volume. The second paper brings two different approaches to present a mathematical model that describes the curve response an EFBG, from a reference calibration curve. The extrapolation approach, which uses the spectral shift verified in the etching process, is of simple application and requires only the refractive index of the external environment. The interpolation approach, which is more complex, presents greater accuracy to the experimental results. The models were applied for refractive indexes ranging from 1.333 to 1.458, for sensors operation from 1544.84 nm to 1552.70 nm range. The largest deviations found between the estimated and experimental values were 0.26 nm and 0.41 nm, for interpolation and extrapolation, respectively. The proposed mathematical models were able to successfully estimate the curve response of different EFBGs diameters, showing up to be a useful tool to estimate the sensor´s sensitivity before its production. The third paper reports the birefringence effect verified after the deposition of an organic film over an EFBG for ammonia detection. The film, resulted from the deposition of a perylene derivative and the PCDTBT copolymer solution in chlorobenzene, induced a separation of the EFBG reflected peaks, which allowed ammonia detection in the range from 3 ppm to 41,700 ppm. The observed peaks presented different sensitivities, indicating the potential for multi-parameter measurement.